Replication Redux : The Reproducibility Crisis and the Case of Deworming - Ozier, Owen (World Bank, Washington, DC, 2019)
In 2004, a landmark study showed that an inexpensive medication to treat parasitic worms could improve health and school attendance for millions of children in many developing countries. Eleven years later, a headline in the Guardian reported that this treatment, deworming, had been "debunked." The pronouncement followed an effort to replicate and re-analyze the original study, as well as an update to a systematic review of the effects of deworming. This story made waves amidst discussion of a reproducibility crisis in some of the social sciences. This paper explores what it means to "replicate" and "reanalyze" a study, both in general and in the specific case of deworming. The paper reviews the broader replication efforts in economics, then examines the key findings of the original deworming paper in light of the "replication," "reanalysis," and "systematic review." The paper also discusses the nature of the link between this single paper's findings, other papers' findings, and any policy recommendations about deworming. This example provides a perspective on the ways replication and reanalysis work, the strengths and weaknesses of systematic reviews, and whether there is, in fact, a reproducibility crisis in economics.